Phytoplankton diversity as a health indicator of coastal ecosystems in Prigi Bay, Trenggalek District, East Java, Indonesia - CATUR RETNANINGDYAH; LUCHMAN HAKIM; ENDANG ARISOESILANINGSIH; SUMANI SUMANI; RAHMANTA SETIAHADI; MUKHTASOR MUKHTASOR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Retnaningdyah C, Hakim L, Arisoesilaningsih E, Sumani, Setiahadi R, Mukhtasor. 2025. Phytoplankton diversity as a health indicator of coastal ecosystems in Prigi Bay, Trenggalek District, East Java, Indonesia. Biodiversitas 26: 2198-2209. This study aims to evaluate the water quality of several coastal ecosystems in the Prigi Bay, Watulimo Sub-district, Trenggalek District, East Java, Indonesia, based on water physicochemical parameters and phytoplankton diversity as bioindicators. Water and plankton sampling were conducted in six coastal ecosystems (Beach of Pasir Putih, Karanggongso, Mutiara, Guo Boto, Prigi, and Karang Pegat). The water physicochemical parameters evaluated include DO, TSS, turbidity, salinity, pH, conductivity, BOD, nitrate, orthophosphate, H2S, and oil-grease. A total of 10 L of water was filtered with a plankton net. Then, the phytoplankton species were identified, and the abundance of each type was calculated. The data obtained were used to determine taxa richness, total density, evenness, dominance index, diversity index, Trophic Diatom Index (TDI), and Percentage Pollution Tolerant Value (%PTV). The study results showed that the physical-chemical quality of water in all research areas met the national and international quality standards concerning seawater quality standards for marine biota, except nitrate, orthophosphate, and oil-grease. A total of 40 species were found in the six coastal ecosystems in the Watulimo area. The abundance of phytoplankton from the Bacillariophyceae was always the highest in all locations, ranging from 67-78%. Phytoplankton diversity is relatively high (4.38-4.84). There is no species dominance or even distribution. The quality of water in coastal ecosystems in the Watulimo area, based on the TDI, is classified as eutrophic. Based on %PTV, there is no indication of organic material pollution except for the Prigi Beach ecosystem, which is included in the lightly polluted organic material category. High human activities around Prigi Beach have impacted the increasing turbidity and orthophosphate content, resulting in high levels of eutrophication and organic material pollution, as indicated by an increase in %PTV and TDI values.